ULTRA-FAST SYNTHESIS OF CURCUMIN-LOADED SILVER NANOPARTICLES: IMPROVED PHYSICOCHEMICAL PROPERTIES FOR DRUG DELIVERY - LI, CHONG XUE; ELHASSAN, GAMAL OSMAN; ABDOUN, SIHAM A.; KHAN, RIYAZ AHMED; GOYAL, MANOJ; BANSAL, MONIKA; MOHAMED, JAMAL MOIDEEN MUTHU (International Journal of Applied Pharmaceutics, 2025)
Objective: This study focused on the green synthesis of silver nanoparticles (AgNPs) using fresh garlic extract (Allium sativum-AS) as a reducing agent for the efficient delivery of curcumin (CuR), a natural anti-cancer agent used in breast cancer therapy. Methods: The study began with the preparation of fresh AS, which was then mixed with silver nitrate (AgNO₃) solution and CuR solution under sunlight for the green synthesis of stable CuR-loaded nanoparticles (C-AgNPs). This method not only offered an eco-friendly approach to the synthesis of C-AgNPs but also highlighted the potential physicochemical characterization of AS and CuR in this context. Moreover, this study assesses the characteristics of the resulting C-AgNPs and conducts a comparative analysis with different formulations to evaluate their efficacy. Results: The prepared C-AgNPs, characterized by Fourier-Transform Infrared Spectroscopy (FTIR), indicated that CuR, silver nitrate (AgNO₃), and AS extract were successfully incorporated, confirming the successful synthesis. The optimized preparation, referred to as AgNP1, demonstrated an entrapment efficacy of 74.24±5.87%, a drug loading of 95.99±7.81%, and a drug content of 96.11±7.82%. Additionally, the cumulative percentage of drug release was found to be 57.12±2.76% at 180 min. The drug was successfully loaded into the C-AgNPs, exhibiting physicochemical compatibility without any adverse chemical interactions with the additives used. Conclusion: In conclusion, this study demonstrated that nanoparticle-based drug delivery systems offer a significant advancement over conventional therapies by providing controlled and efficient drug delivery, thereby improving therapeutic outcomes.